Preparation process of nano silicon dioxide microspheres with high dispersion stability
By preparing high -decentralized nano -nano -sanxide microbolis, the polyolefin layer is used to cover the modification technology, which solves the problem of insufficient decentralization of nano -silicon dioxide in rubber materials. Stability enhances the performance of rubber products.
Patent Information
- Application Number
- CN202411482903.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
The dispersion of nanosilica in rubber materials needs to be further improved, mainly due to the agglomeration between the particles and the oleophobic properties, resulting in insufficient dispersion.
By preparing nano-silica microspheres with high dispersion stability, (e)-(9ci)-3-(4-pyridine)-2-propionamide and dioctyl maleate are used to coat and modify the modified particles. , forming nano-silica microspheres coated with a polyolefin layer to improve its compatibility with rubber materials.
It significantly improves the decentralization and stability of nano nanoxide microspheres in rubber, reduce the phenomenon of reunion between particles, and enhance the mechanical performance, abrasion resistance and aging resistance of rubber products.
Smart Images

Figure CN119350887A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano silicon dioxide preparation, and in particular to a preparation process of nano silicon dioxide microspheres with high dispersion stability. Background Art
[0002] With the continuous development of materials science, nanomaterials are increasingly used in various fields. Among them, nano-silicon dioxide has shown great application potential in the rubber industry due to its unique physical and chemical properties, such as high specific surface area, good chemical stability and excellent reinforcement performance, especially in the reinforcement and modification of natural rubber. The introduction of nano-silicon dioxide can significantly improve the mechanical properties, wear resistance and aging resistance of rubber products.
[0003] Due to the extremely small particle size of nano-silica, its specific surface area increases dramatically. A high specific surface area means an increase in the number of surface atoms. The surface of nano-silica is rich in hydroxyl groups, which easily form hydrogen bonds, causing the particles to tend to agglomerate and form agglomerates, thereby reducing its dispersibility in the rubber matrix. In addition, the presence of hydroxyl groups also makes nano-silica oleophobic and has a weaker binding ability with rubber macromolecules, further affecting its dispersibility in the rubber matrix.
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation process of nano-silicon dioxide microspheres with high dispersion stability, so as to solve the technical problem in the prior art that the dispersibility of nano-silicon dioxide in rubber materials needs to be further improved.
[0006] The purpose of the present invention can be achieved by the following technical scheme: A preparation process of nano-silicon dioxide microspheres with high dispersion stability comprises the following steps:
[0007] S1. Add (e)-(9ci)-3-(4-pyridine)-2-propionamide, dioctyl maleate, modified microparticles and emulsion into a three-necked flask and stir. Raise the temperature of the three-necked flask to 75-85° C., add an initiator into the three-necked flask, keep the temperature for reaction for 2-3 hours, and perform post-treatment to obtain a crude product of nano-silica microspheres.
[0008] The synthetic reaction formula of crude nano-silica microspheres is:
[0009]
[0010] The synthetic reaction principle of crude nano-silica microspheres is:
[0011] (e)-(9ci)-3-(4-pyridine)-2-propionamide, dioctyl maleate and modified particles form tiny spheres in an emulsion having a coating structure with the modified particles as a core and (e)-(9ci)-3-(4-pyridine)-2-propionamide and dioctyl maleate as a shell. Under the action of an initiator, (e)-(9ci)-3-(4-pyridine)-2-propionamide, dioctyl maleate and the unsaturated double bonds on the modified particles undergo free radical addition reactions to form a thin polyolefin coating layer on the outside of the modified particles, thereby preparing a crude nano-silica microsphere product.
[0012] S2. Add the crude nano-silica microspheres and the dispersion into a three-necked flask, place the three-necked flask in a water bath at a temperature of 55-65°C, perform ultrasonic dispersion for 5-7 hours, fix the three-necked flask on an iron stand, add cyclohexane into the three-necked flask, stir and disperse at room temperature for 40-50 minutes, and perform post-treatment to obtain nano-silica microspheres.
[0013] Furthermore, in step S1, the amount ratio of the (e)-(9ci)-3-(4-pyridine)-2-propionamide, dioctyl maleate, modified particles, emulsion and initiator is 1g:3g:7g:30mL:0.04g, the initiator is azobisisobutyronitrile, the emulsion is composed of toluene, deionized water, ethylene glycol, sodium dodecylbenzenesulfonate and Tween-20 in an amount ratio of 100mL:60mL:15mL:3-5g:1-2g, the stirring speed is 650-750r / min, and the post-treatment includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, filtered, the filter cake is washed with acetone 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain a crude nano-silica microsphere.
[0014] Furthermore, in step S2, the ratio of the crude nano-silica microspheres, the dispersion and cyclohexane is 1g:6-8mL:3mL, the dispersion is composed of toluene, cyclohexane and lauroyl diethanolamine in a ratio of 10mL:3mL:0.5g, and the post-treatment includes: after the reaction is completed, filtering, washing the filter cake with cyclohexane for 3 times and then drying, transferring the filter cake to a drying oven at a temperature of 40-50°C, and vacuum drying to constant weight to obtain nano-silica microspheres.
[0015] Furthermore, the preparation method of the modified microparticles is: adding nano-silicon dioxide microparticles, N,N-dimethylformamide, and a catalyst into a three-necked flask and stirring, adding 3-butene-1-ol into a reactor, raising the temperature of the three-necked flask to 80-90° C., keeping the temperature for reaction for 6-8 hours, and obtaining the modified microparticles after post-treatment.
[0016] The synthetic reaction formula of the modified particles is:
[0017]
[0018] The synthetic reaction principle of modified particles is:
[0019] Under the action of the catalyst, the alcoholic hydroxyl group on 3-butene-1-ol undergoes a substitution reaction with the halogen on the surface of the nano-silica particles to generate modified particles with olefin modification.
[0020] Furthermore, the dosage ratio of the nano-silica particles, N,N-dimethylformamide, catalyst and 3-butene-1-ol is 5g:30mL:0.1-0.2g:2g, the catalyst is composed of n-tetrabutylammonium hydrogen sulfate and potassium hydroxide in a weight ratio of 1:3, and the post-treatment includes: after the reaction is completed, filtering, washing the filter cake with 60wt% methanol for 3 times and then drying, transferring the filter cake to a drying oven at a temperature of 50-60°C, and vacuum drying to constant weight to obtain modified particles.
[0021] Furthermore, the nano silicon dioxide particles are obtained by processing the following steps:
[0022] A1. Add glacial acetic acid and deionized water into a three-necked flask and stir. Raise the temperature of the three-necked flask to 60-70°C. Add ethyl orthosilicate into the three-necked flask and keep the temperature to react for 10-12 hours to obtain a precursor solution.
[0023] A2. Add emulsifier to the three-necked flask containing the precursor solution and stir for 30-50 minutes. The temperature of the three-necked flask is raised to 60-70°C. Mixed ethyl silicate is added to the three-necked flask in three batches. The interval between adjacent batches is 6-8 hours. The reaction is kept warm. After the addition is completed, the mixture is kept warm and stirred for 10-12 hours. Nano-silica particles are obtained by post-treatment.
[0024] The synthetic reaction formula of nano-silicon dioxide particles is:
[0025]
[0026] In the formula, is the core particle in the precursor solution, It is nano silicon dioxide particles.
[0027] The synthetic reaction principle of nano-silicon dioxide particles is:
[0028] In an acidic aqueous solution, the siloxyethane bonds on the tetraethyl orthosilicate are hydrolyzed to form a hydrolysis product containing silanol groups. The hydrolysis product further undergoes a condensation reaction in the acidic aqueous solution to form core particles with an oligosiloxane structure. The addition of an emulsifier promotes the emulsification of the reaction system, and the mixed tetraethyl orthosilicate is dispersed in the precursor solution in the form of tiny droplets to form an emulsion. In the emulsion, the mixed tetraethyl orthosilicate continues to hydrolyze and condense to form a sol containing halogen modification. As the reaction proceeds, the sol particles interact with each other, and a gel network is gradually formed on the outside of the core particles. In the post-treatment process, isopropanol is used to wash and replace the solvent in the gel to promote the solidification of the gel structure to obtain nano-silica particles.
[0029] Furthermore, in step A1, the usage ratio of glacial acetic acid, deionized water and tetraethyl orthosilicate is 0.8-1g:100mL:10g, and the stirring speed of the three-necked flask is 500-550r / min.
[0030] Further, in step A2, the amount ratio of the precursor solution, the emulsifier and the mixed ethyl silicate is 100mL:20mL:12-17g, the emulsifier is composed of n-hexane, dodecylphenol polyoxyethylene ether, Tween-20 and the stabilizer in an amount ratio of 10mL:2g:1g:5g, the stabilizer is composed of urea, polyethylene glycol, and sodium citrate in a weight ratio of 1:2:2, and the mixed ethyl silicate is composed of ethyl orthosilicate, 2-chloroethyltriethoxysilane massage The stirring speed of the three-necked flask is 600-650r / min, and the post-treatment comprises: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, suction filtration is performed, the filter cake and isopropanol are added to the three-necked flask at a dosage ratio of 1g:6mL, stirred at room temperature for 30-40min, suction filtered, the filter cake is washed with isopropanol 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 110-120°C, and vacuum dried to constant weight to obtain nano silicon dioxide particles.
[0031] The present invention has the following beneficial effects:
[0032] 1. The nano-silica microspheres with high dispersion stability of the present invention are prepared by using tetraethyl orthosilicate as a monomer to obtain a precursor solution containing oligosiloxane structure core particles, which is emulsified by an emulsifier to form a composite structure of a mixed tetraethyl orthosilicate with a microstructure and core particles in the precursor solution, and 2-chloroethyltriethoxysilane is used as a comonomer to change the hydrolysis and polycondensation rates of the silicon source, thereby affecting the growth rate and particle size distribution of the nano-particles. The selection of the molar ratio of 3:1 is based on experimental optimization to obtain nano-silica particles with a particle size of 50-70 nm, 2- Chloroethyltriethoxysilane is introduced as a reaction monomer to introduce halogen chlorine into the nano-silica particles, and a substitution reaction occurs with 3-butene-1-ol under the action of a catalyst to form modified particles with an unsaturated bond modification layer on the nano-silica particles; the modified particles undergo a free radical addition reaction with an unsaturated bond-containing monomer in an emulsion environment to prepare polyolefin-coated nano-silica microspheres, and high-molecular-weight polyolefin is used as a compatibilizer to improve the compatibility between the nano-silica microspheres and the rubber material, thereby improving the dispersibility and stability of the nano-silica microspheres in the rubber.
[0033] 2. The nano silicon dioxide microspheres with high dispersion stability of the present invention are prepared by mixing urea, polyethylene glycol and sodium citrate as a stabilizer with n-hexane, dodecylphenol polyoxyethylene ether and Tween-20 to obtain an emulsifier. The polyethylene glycol in the stabilizer, as a high molecular polymer, can increase the viscosity of the emulsion, reduce the movement and collision of droplets, and help maintain the stability of the emulsion. Urea is an organic compound containing an amide group, which can partially ionize amino and carbonyl groups in an aqueous solution. Sodium citrate is a strong base weak acid salt, which can ionize citrate ions and sodium ions in an aqueous solution. These ions can interact with silicate ions in the reaction system, play a template-guiding role in the formation and growth process of nanoparticles, and affect the particle size and morphology of the nanoparticles. The emulsifier can disperse the silicon source into tiny droplets in the preparation process of the nanoparticles, and adjust the size of the droplets by coordinating with the stirring speed, thereby controlling the nucleation and growth process of the nanoparticles, and preparing nano silicon dioxide particles with stable size.
[0034] 3. The nano-silica microspheres with high dispersion stability of the present invention are coated and modified by (e)-(9ci)-3-(4-pyridine)-2-propionamide and dioctyl maleate in an emulsion environment to form nano-silica microspheres coated and modified with a polyolefin layer. The polyolefin structure coating layer forms a physical barrier on the surface of the silica particles. This barrier prevents direct contact and agglomeration between particles through a steric hindrance effect. In addition, the nitrogen atoms and carbonyl oxygen atoms in the amide group in the polyolefin layer can interact with other polar groups through hydrogen bonds, while the long-chain alkyl part of dioctyl maleate may increase the non-polar interaction with the rubber matrix. This interaction helps to enhance the interface compatibility between the silica particles and the rubber matrix, making the particles more easily dispersed in the rubber, reducing agglomeration, and improving the dispersion level and dispersion stability of the nano-silica microspheres in the rubber material. During the mixing and molding process, the coating layer can also reduce the damage and entanglement of the silica particles to the rubber molecular chain, making the processing process smoother. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 is the XRD diagram of the nano-silica microspheres in the present invention;
[0037] Figure 2 is a SEM image of the nano silicon dioxide particles in the present invention;
[0038] Figure 3 This is a physical picture of the nano-silica microspheres in the present invention. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] This embodiment provides a preparation process of nano-silicon dioxide microspheres with high dispersion stability, comprising the following steps:
[0042] S1. Preparation of Nano-Silica Particles
[0043] Weigh: 4 g of glacial acetic acid and 500 mL of deionized water, add them into a three-necked flask and stir, set the stirring speed to 500 r / min, raise the temperature of the three-necked flask to 60°C, add 50 g of ethyl orthosilicate into the three-necked flask, keep the temperature for reaction for 10 hours, and obtain a precursor solution;
[0044] Urea, polyethylene glycol 400 and sodium citrate are uniformly mixed in a weight ratio of 1:2:2 to obtain a stabilizer;
[0045] n-hexane, dodecylphenol polyoxyethylene ether, Tween-20 and stabilizer are uniformly mixed in an amount ratio of 10 mL: 2 g: 1 g: 5 g to obtain an emulsifier;
[0046] Mixing ethyl orthosilicate and 2-chloroethyltriethoxysilane in a molar ratio of 3:1 to obtain mixed ethyl silicate;
[0047] Add 100 g of emulsifier to a three-necked flask containing 500 mL of precursor solution, set the stirring speed to 600 r / min, stir for 30 min, raise the temperature of the three-necked flask to 60°C, add 60 g of mixed ethyl silicate to the three-necked flask in three batches, with an interval of 6 h between adjacent batches, and keep warm for reaction. After the addition is completed, keep warm and stir for 10 h. After the reaction is completed, lower the temperature of the three-necked flask to room temperature, filter, add the filter cake and isopropanol in a ratio of 1 g:6 mL to the three-necked flask, stir at room temperature for 30 min, filter, wash the filter cake with isopropanol 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 110°C, and vacuum dry it to constant weight to obtain nano-silica particles.
[0048] S2. Preparation of modified microparticles
[0049] Tetrabutylammonium hydrogen sulfate and potassium hydroxide are uniformly mixed in a weight ratio of 1:3 to obtain a catalyst;
[0050] Weigh: 50 g of nano-silica particles, 300 mL of N,N-dimethylformamide, and 1 g of catalyst, add them into a three-necked flask and stir, add 20 g of 3-butene-1-ol into the reactor, raise the temperature of the three-necked flask to 80°C, and keep the reaction for 6 hours. After the reaction is completed, filter it, wash the filter cake with 60wt% methanol three times and then dry it, transfer the filter cake to a drying oven at a temperature of 50°C, and vacuum dry it to constant weight to obtain modified particles.
[0051] S3. Preparation of crude nano-silica microspheres
[0052] Toluene, deionized water, ethylene glycol, sodium dodecylbenzene sulfonate and Tween-20 were mixed uniformly in a dosage ratio of 100 mL: 60 mL: 15 mL: 3 g: 1 g to obtain an emulsion;
[0053] Weigh: 10 g of (e)-(9ci)-3-(4-pyridine)-2-propionamide, 30 g of dioctyl maleate, 70 g of modified microparticles and 300 mL of emulsion, add into a three-necked flask and stir, set the stirring speed to 650 r / min, raise the temperature of the three-necked flask to 75°C, add 0.4 g of initiator into the three-necked flask, keep warm and react for 2 hours, after the reaction is completed, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with acetone 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain a crude nano-silica microsphere.
[0054] S4. Preparation of Nano-Silica Microspheres
[0055] Toluene, cyclohexane and lauroyl diethanolamine were mixed uniformly in a ratio of 10 mL: 3 mL: 0.5 g to obtain a dispersion;
[0056] Weigh: 50 g of crude nano-silica microspheres and 300 mL of dispersion liquid are added into a three-necked flask, the three-necked flask is placed in a water bath with a water bath temperature of 55°C, ultrasonically dispersed for 5 hours, the three-necked flask is fixed on an iron stand, 150 mL of cyclohexane is added to the three-necked flask, stirred and dispersed at room temperature for 40 minutes, after the reaction is completed, filtered, the filter cake is washed with cyclohexane 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 40°C, and vacuum dried to constant weight to obtain nano-silica microspheres.
[0057] Example 2
[0058] This embodiment provides a preparation process of nano-silicon dioxide microspheres with high dispersion stability, comprising the following steps:
[0059] S1. Preparation of Nano-Silica Particles
[0060] Weigh: 4.5 g of glacial acetic acid and 500 mL of deionized water, add them into a three-necked flask and stir, set the stirring speed to 525 r / min, raise the temperature of the three-necked flask to 65°C, add 50 g of ethyl orthosilicate into the three-necked flask, keep the temperature for reaction for 11 hours, and obtain a precursor solution;
[0061] Urea, polyethylene glycol 400 and sodium citrate are uniformly mixed in a weight ratio of 1:2:2 to obtain a stabilizer;
[0062] n-hexane, dodecylphenol polyoxyethylene ether, Tween-20 and stabilizer are uniformly mixed in an amount ratio of 10 mL: 2 g: 1 g: 5 g to obtain an emulsifier;
[0063] Mixing ethyl orthosilicate and 2-chloroethyltriethoxysilane in a molar ratio of 3:1 to obtain mixed ethyl silicate;
[0064] Add 100 g of emulsifier to a three-necked flask containing 500 mL of precursor solution, set the stirring speed to 625 r / min, stir for 40 min, raise the temperature of the three-necked flask to 65°C, add 73 g of mixed ethyl silicate to the three-necked flask in three batches, with an interval of 7 h between adjacent batches, and keep warm for reaction. After the addition is completed, keep warm and stir for 11 h. After the reaction is completed, lower the temperature of the three-necked flask to room temperature, filter, add the filter cake and isopropanol in a ratio of 1 g:6 mL to the three-necked flask, stir at room temperature for 35 min, filter, wash the filter cake with isopropanol 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 115°C, and vacuum dry it to constant weight to obtain nano-silica particles.
[0065] S2. Preparation of modified microparticles
[0066] Tetrabutylammonium hydrogen sulfate and potassium hydroxide are uniformly mixed in a weight ratio of 1:3 to obtain a catalyst;
[0067] Weigh: 50 g of nano-silica particles, 300 mL of N,N-dimethylformamide, and 1.5 g of catalyst, add them into a three-necked flask and stir, add 20 g of 3-butene-1-ol into the reactor, raise the temperature of the three-necked flask to 85°C, and keep the reaction for 7 hours. After the reaction is completed, filter it, wash the filter cake with 60wt% methanol three times and then dry it, transfer the filter cake to a drying oven at a temperature of 55°C, and vacuum dry it to constant weight to obtain modified particles.
[0068] S3. Preparation of crude nano-silica microspheres
[0069] Toluene, deionized water, ethylene glycol, sodium dodecylbenzene sulfonate and Tween-20 were mixed uniformly in a dosage ratio of 100 mL: 60 mL: 15 mL: 4 g: 1.5 g to obtain an emulsion;
[0070] Weigh: 10 g of (e)-(9ci)-3-(4-pyridine)-2-propionamide, 30 g of dioctyl maleate, 70 g of modified microparticles and 300 mL of emulsion, add into a three-necked flask and stir, set the stirring speed to 700 r / min, raise the temperature of the three-necked flask to 80°C, add 0.4 g of initiator into the three-necked flask, keep warm and react for 2.5 hours, after the reaction is completed, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with acetone 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry it to constant weight to obtain a crude nano-silica microsphere.
[0071] S4. Preparation of Nano-Silica Microspheres
[0072] Toluene, cyclohexane and lauroyl diethanolamine were mixed uniformly in a ratio of 10 mL: 3 mL: 0.5 g to obtain a dispersion;
[0073] Weigh: 50 g of crude nano-silica microspheres and 350 mL of dispersion liquid are added into a three-necked flask, the three-necked flask is placed in a water bath at a water bath temperature of 60°C, ultrasonically dispersed for 6 hours, the three-necked flask is fixed on an iron stand, 150 mL of cyclohexane is added to the three-necked flask, stirred and dispersed at room temperature for 45 minutes, after the reaction is completed, filtered, the filter cake is washed with cyclohexane 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 45°C, and vacuum dried to constant weight to obtain nano-silica microspheres.
[0074] Example 3
[0075] This embodiment provides a preparation process of nano-silicon dioxide microspheres with high dispersion stability, comprising the following steps:
[0076] S1. Preparation of Nano-Silica Particles
[0077] Weigh: 5 g of glacial acetic acid and 500 mL of deionized water, add them into a three-necked flask and stir, set the stirring speed to 550 r / min, raise the temperature of the three-necked flask to 70°C, add 50 g of ethyl orthosilicate into the three-necked flask, keep the temperature for reaction for 12 hours, and obtain a precursor solution;
[0078] Urea, polyethylene glycol 400 and sodium citrate are uniformly mixed in a weight ratio of 1:2:2 to obtain a stabilizer;
[0079] n-hexane, dodecylphenol polyoxyethylene ether, Tween-20 and stabilizer are uniformly mixed in an amount ratio of 10 mL: 2 g: 1 g: 5 g to obtain an emulsifier;
[0080] Mixing ethyl orthosilicate and 2-chloroethyltriethoxysilane in a molar ratio of 3:1 to obtain mixed ethyl silicate;
[0081] Add 100 g of emulsifier to a three-necked flask containing 500 mL of precursor solution, set the stirring speed to 650 r / min, stir for 50 min, raise the temperature of the three-necked flask to 70°C, add 85 g of mixed ethyl silicate to the three-necked flask in three batches, with an interval of 8 h between adjacent batches, and keep warm for reaction. After the addition is completed, keep warm and stir for 12 h. After the reaction is completed, lower the temperature of the three-necked flask to room temperature, filter, add the filter cake and isopropanol in a ratio of 1 g:6 mL to the three-necked flask, stir at room temperature for 40 min, filter, wash the filter cake with isopropanol 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 120°C, and vacuum dry it to constant weight to obtain nano-silica particles.
[0082] S2. Preparation of modified microparticles
[0083] Tetrabutylammonium hydrogen sulfate and potassium hydroxide are uniformly mixed in a weight ratio of 1:3 to obtain a catalyst;
[0084] Weigh: 50 g of nano-silica particles, 300 mL of N,N-dimethylformamide, and 2 g of catalyst, add them into a three-necked flask and stir, add 20 g of 3-butene-1-ol into the reactor, raise the temperature of the three-necked flask to 90°C, and keep the reaction for 8 hours. After the reaction is completed, filter it, wash the filter cake with 60wt% methanol three times and then dry it, transfer the filter cake to a drying oven at a temperature of 60°C, and vacuum dry it to constant weight to obtain modified particles.
[0085] S3. Preparation of crude nano-silica microspheres
[0086] Toluene, deionized water, ethylene glycol, sodium dodecylbenzene sulfonate and Tween-20 were mixed uniformly in a dosage ratio of 100 mL: 60 mL: 15 mL: 5 g: 2 g to obtain an emulsion;
[0087] Weigh: 10 g of (e)-(9ci)-3-(4-pyridine)-2-propionamide, 30 g of dioctyl maleate, 70 g of modified microparticles and 300 mL of emulsion, add into a three-necked flask and stir, set the stirring speed to 750 r / min, raise the temperature of the three-necked flask to 85°C, add 0.4 g of initiator into the three-necked flask, keep warm and react for 3 hours, after the reaction is completed, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with acetone 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 80°C, and vacuum dry it to constant weight to obtain a crude nano-silica microsphere.
[0088] S4. Preparation of Nano-Silica Microspheres
[0089] Toluene, cyclohexane and lauroyl diethanolamine were mixed uniformly in a ratio of 10 mL: 3 mL: 0.5 g to obtain a dispersion;
[0090] Weigh: 50 g of crude nano-silica microspheres and 400 mL of dispersion liquid are added into a three-necked flask, the three-necked flask is placed in a water bath at a water bath temperature of 65°C, ultrasonically dispersed for 7 hours, the three-necked flask is fixed on an iron stand, 150 mL of cyclohexane is added to the three-necked flask, stirred and dispersed at room temperature for 50 minutes, after the reaction is completed, filtered, the filter cake is washed with cyclohexane 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 50°C, and vacuum dried to constant weight to obtain nano-silica microspheres.
[0091] Comparative Example 1
[0092] The difference between this comparative example and Example 3 is that no stabilizer is added to the emulsifier in step S1.
[0093] Comparative Example 2
[0094] The difference between this comparative example and Example 3 is that no 2-chloroethyltriethoxysilane is added to the mixed ethyl silicate in step S1.
[0095] Comparative Example 3
[0096] The difference between this comparative example and Example 3 is that step S3 is omitted, and the modified particles prepared in step S2 are used as nano-silica microspheres.
[0097] Performance Test:
[0098] The dispersion grade and instability index of the nano-silica microspheres prepared in Examples 1-3 and Comparative Examples 1-3 were tested, wherein the dispersion grade was determined by visually observing the dispersion grade of the sample in natural rubber according to the standard GB / T 6030-2006 "Rapid comparison method for evaluating the dispersion of carbon black and carbon black / silica in rubber", and the instability index of the sample in natural rubber was determined according to GB / T38431-2019 "Static multiple light scattering method for evaluating the stability of particle dispersion system". The specific test results are shown in Table 1:
[0099] Table 1-Performance test data of the sample
[0100]
[0101] Data Analysis:
[0102] Comparative analysis of the data in the above table shows that the visual dispersion grade of the nano-silica microspheres prepared by the present invention in natural rubber reaches 9-10, the instability index is reduced to 0.102%, and various performance parameters are better than those of the comparative example, indicating that the present invention is to prepare a precursor solution containing oligosiloxane structure core particles by using tetraethyl orthosilicate as a monomer, and to grow a halogen-containing mixed ethyl silicate on the outside of the core particles in an emulsified system to prepare nano-silica particles, and to improve the compatibility between the nano-silica microspheres and the rubber material by coating the outside of the nano-silica particles with a polyolefin layer structure, thereby improving the dispersibility and stability of the nano-silica microspheres in the rubber.
[0103] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0104] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0105] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A process for preparing nano-silica microspheres with high dispersion stability, characterized in that: The following steps are involved: S1. Add (e)-(9ci)-3-(4-pyridine)-2-propionamide, dioctyl maleate, modified microparticles and emulsion into a three-necked flask and stir. Raise the temperature of the three-necked flask to 75-85° C., add an initiator into the three-necked flask, keep the temperature for reaction for 2-3 hours, and perform post-treatment to obtain a crude product of nano-silica microspheres. S2. Add the crude nano-silica microspheres and the dispersion into a three-necked flask, place the three-necked flask in a water bath at a temperature of 55-65°C, perform ultrasonic dispersion for 5-7 hours, fix the three-necked flask on an iron stand, add cyclohexane into the three-necked flask, stir and disperse at room temperature for 40-50 minutes, and perform post-treatment to obtain nano-silica microspheres.
2. The process for preparing a nano-silica microsphere with high dispersion stability according to claim 1, characterized in that: In step S1, the amount ratio of the (e)-(9ci)-3-(4-pyridine)-2-propionamide, dioctyl maleate, modified microparticles, emulsion and initiator is 1g:3g:7g:30mL:0.04g, the initiator is azobisisobutyronitrile, the emulsion is composed of toluene, deionized water, ethylene glycol, sodium dodecylbenzenesulfonate and Tween-20 in a ratio of 100mL:60mL:15mL:3-5g:1-2g, and the stirring speed is 650-750r / min.
3. The preparation process of a nano-silica microsphere with high dispersion stability according to claim 1, characterized in that: In step S2, the ratio of the crude nano-silica microspheres, the dispersion and cyclohexane is 1 g:6-8 mL:3 mL, and the dispersion is composed of toluene, cyclohexane and lauroyl diethanolamine in a ratio of 10 mL:3 mL:0.5 g.
4. The process for preparing a nano-silica microsphere with high dispersion stability according to claim 1, characterized in that: The preparation method of the modified microparticles comprises: adding nano silicon dioxide microparticles, N,N-dimethylformamide and a catalyst into a three-necked flask and stirring, adding 3-butene-1-ol into a reaction kettle, raising the temperature of the three-necked flask to 80-90° C., keeping the temperature for reaction for 6-8 hours, and performing post-treatment to obtain the modified microparticles.
5. The process for preparing nano-silica microspheres with high dispersion stability according to claim 4, characterized in that: The dosage ratio of the nano silicon dioxide particles, N,N-dimethylformamide, the catalyst and 3-butene-1-ol is 5g:30mL:0.1-0.2g:2g, and the catalyst is composed of n-tetrabutylammonium hydrogen sulfate and potassium hydroxide in a weight ratio of 1:
3.
6. The process for preparing nano-silica microspheres with high dispersion stability according to claim 4, characterized in that: The nano silicon dioxide particles are obtained by processing the following steps: A1. Add glacial acetic acid and deionized water into a three-necked flask and stir. Raise the temperature of the three-necked flask to 60-70°C. Add ethyl orthosilicate into the three-necked flask and keep the temperature to react for 10-12 hours to obtain a precursor solution. A2. Add emulsifier to the three-necked flask containing the precursor solution and stir for 30-50 minutes. The temperature of the three-necked flask is raised to 60-70°C. Mixed ethyl silicate is added to the three-necked flask in three batches. The interval between adjacent batches is 6-8 hours. The reaction is kept warm. After the addition is completed, the mixture is kept warm and stirred for 10-12 hours. Nano-silica particles are obtained by post-treatment.
7. The process for preparing nano-silica microspheres with high dispersion stability according to claim 6, characterized in that: In step A1, the usage ratio of glacial acetic acid, deionized water and tetraethyl orthosilicate is 0.8-1g:100mL:10g, and the stirring speed of the three-necked flask is 500-550r / min.
8. The process for preparing nano-silica microspheres with high dispersion stability according to claim 6, characterized in that: In step A2, the amount ratio of the precursor solution, the emulsifier and the mixed ethyl silicate is 100mL:20mL:12-17g, the emulsifier is composed of n-hexane, dodecylphenol polyoxyethylene ether, Tween-20 and the stabilizer in an amount ratio of 10mL:2g:1g:5g, the stabilizer is composed of urea, polyethylene glycol and sodium citrate in a weight ratio of 1:2:2, the mixed ethyl silicate is composed of ethyl orthosilicate and 2-chloroethyltriethoxysilane in a molar ratio of 3:1, and the stirring speed of the three-necked flask is 600-650r / min.